Differentiation of a human leukemia cell line and expression of collagenase inhibitor. - Bar-Shavit, Z (1985)
A human collagenase inhibitor (CI) of Mr 28,500 has been extensively characterized in skin fibroblasts and identified in a variety of connective tissues. Because human alveolar macrophages synthesize and secrete both a collagenase and CI that are immunologically and functionally identical to their counterparts in fibroblasts, we studied the production of such proteins by an immature human cell line (HL60) that can be induced to differentiate along monocytic or granulocytic pathways. The cells failed to synthesize collagenase under any culture condition tested. However, upon exposure to 1,25-dihydroxyvitamin D3 or phorbol esters (PMA), both of which promote monocytic differentiation of HL60, these cells synthesized and released CI in a dose-dependent manner. Furthermore, the extent of CI expression was paralleled by the acquisition by such cells of the monocytic marker 63D3, indicating that inhibitor production and differentiation are closely correlated. This CI was immunologically and functionally identical to that produced by human macrophages and human skin fibroblasts. The quantity of CI synthesized by PMA-stimulated cells was 3- to 5-fold greater than produced by human alveolar macrophages, approximately equal to 1 microgram per 10(6) cells per day. In contrast, undifferentiated HL60 cells produced little or no detectable CI (less than or equal to 10-20 ng per 10(6) cells per day). Interestingly, when HL60 cells were stimulated to undergo granulocytic differentiation by dimethyl sulfoxide or retinoic acid, they also produced the "monocytic" CI.